Β‐Arrestin‐kinase scaffolds: turn them on or turn them off?. (14th January 2013) - Lin, Alice; DeFea, Kathryn A.
Abstract: G‐protein‐coupled receptors (GPCRs) can signal through heterotrimeric G‐proteins or through β‐arrestins to elicit responses to a plethora of extracellular stimuli. While the mechanisms underlying G‐protein signaling is relatively well understood, the mechanisms by which β‐arrestins regulate the diverse set of proteins with which they associate remain unclear. Multi‐protein complexes are a common feature of β‐arrestin‐dependent signaling. The first two such complexes discovered were the mitogen‐activated kinases modules associated with extracellular regulated kinases (ERK1/2) and Jnk3. Subsequently a number of other kinases have been shown to undergo β‐arrestin‐dependent regulation, including Akt, phosphatidylinositol‐3kinase (PI3K), Lim‐domain‐containing kinase (LIMK), calcium calmodulin kinase II (CAMKII), and calcium calmodulin kinase kinase β (CAMKKβ). Some are positively and some negatively regulated by β‐arrestin association. One of the missing links to understanding these pathways is the molecular mechanisms by which the activity of these kinases is regulated. Do β‐arrestins merely serve as scaffolds to bring enzyme and substrate together or do they have a direct effect on the enzymatic activities of target kinases? Recent evidence suggests that both mechanisms are involved and that the mechanisms by which β‐arrestins regulate kinase activity varies with the target kinase. This review discusses recent advances in the field focusing on 5 kinases for which considerable mechanistic detail and specific sites of interaction have been elucidated. WIREs Syst Biol Med 2013, 5:231–241. doi: 10.1002/wsbm.1203 This article is categorized under: Biological Mechanisms > Cell Signaling Models of Systems Properties and Processes > Mechanistic Models